Determinants of the Financial Performance and Sustainability of Microfinance Institutions in Chandrapur Municipality Nepal - Ghising, Tilak (Nepal Journal of Multidisciplinary Research, 2023)
The financial performance and Level of financial sustainability of microfinance institutions (MFIs) in Chandrapur Municipality is examined in this article. Access to financial services for the most vulnerable social groups has long been a problem that numerous projects and programs are trying to solve. Performance of Microfinance Institutions Various works suggest that the performance of an institution can be understood from two perspectives. This investigation used an exploratory research approach. The data has been collected for adaptation of the services and products to the target clients from Chandrapur Municipality by age and number of year involved in microfinance institutions.